Peningkatan Self-Efficacy Mahasiswa melalui Problem Based Learning (PBL) pada Mata Kuliah Program Linier - Octaria, Dina; Puspasari, Eka Fitri (Jurnal Elemen, 2018)
This study aims to examine the improvement of students self-efficacy in the linear program after learning model of learning problem based learning (PBL) and conventional learning in terms of overall and KAM (high, medium and low). The subjects in this study are students of the fourth semester of the mathematics education program of PGRI Palembang university academic year 2016/2017 which contracted the linier program which amounted to 62 people. This study used quasi-experimental method with pretest group design and non-equivalent postes. The instruments used in this research are KAM test and self-efficacy scale, data analysis using t-test. The result of the research shows that the increase of student self-efficacy in the linear programming courses that get the PBL is better than the students who get conventional learning in terms of overall or KAM (medium, low) even though the value of gain is in low category,while for high KAM are in the medium category.